Patrimônio industrial e memória: a cervejaria Miranda Corrêa - Mendonça, Rosanna Lima de (2020)
The industrial heritage has acquired a sense that goes beyond the aesthetic to become a set of temporal and spatial order in the face of the advance of forgetfulness and the loss of the place's memory. Landscape values, industrial traces, collective memory and artistic heritage are mixed in a continuous space. The building as a place of work can represent different memories in the social and cultural context of the city. So, for the former workers of Cervejaria Amazonense Miranda Corrêa is an industrial heritage? What are the memories connected to the building? As the Free Zone city, Manaus has little discussion of the industry as heritage. Therefore, the present work has as a general objective to understand the appropriation and valorization of the industrial heritage of the former Cervejaria Amazonense Miranda Corrêa through the eyes of former factory workers. The specific objectives will be: To understand the social and geographical changes that occurred due to the inclusion of industry in Manaus at the beginning of the 20th century; Describe the historical process of Cervejaria Amazonense Miranda Corrêa; Understand how the brewery's industrial heritage is appropriated and valued based on the memories and meanings attributed by former factory workers. The work bases the methodology on oral history. Through the collected narratives, it is possible to work with the memories and resignifications pointed out by the narrators, fulfilling the proposed objective of the research. The work intends to bring up the discussion of the industrial heritage constituted from the identity of individuals, bringing the place of speech of former workers and how their experiences contribute to the current vision of the building in the constitution of memory, culture and heritage.